Dari Warga untuk Desa: Peran Komunikasi Partisipatif dalam Pengelolaan Dana Desa - Wa Ode Sitti Nurhaliza (CV. ITTC INDONESIA, 2025)
This article discusses the complexities associated with the administration of village funds in Indonesia, particularly in relation to cases of misuse and corruption at the village level. Despite the primary objective of village funds to improve welfare and promote development in rural areas, the lack of transparency and community participation in the planning and monitoring processes often leads to fund misappropriation. This paper aims to identify the factors contributing to the misuse of village funds and analyze the role of participatory communication in enhancing transparency and accountability in village fund management. Using a literature review method and a qualitative descriptive approach, this study explores various academic sources and cases of village fund misuse in Indonesia. The findings indicate that the main factors contributing to fund misappropriation include the low quality of human resources among village officials, weak community involvement, inadequate oversight, and economic pressures. To address these issues, this article recommends a participatory communication approach that includes increasing access to information through village websites and social media, actively involving the community in planning and monitoring processes, and enhancing the capacity of village officials through training on financial transparency and public communication. Additionally, the role of local organizations such as PKK (Family Welfare Empowerment), Karang Taruna (Youth Organization), and the Village Consultative Body (BPD) should be strengthened in overseeing the use of village funds. By implementing participatory communication effectively, communities can actively engage in every stage of village fund management, thereby improving transparency and accountability while minimizing the potential for misuse. This approach is expected to support more sustainable village development that prioritizes the welfare of the community.